COMMUNITY PARTICIPATION IN PAYING PBB WITHIN THE FRAMEWORK OF LOCAL WISDOM CULTURE - Elwiyani Army; Haliah; Nirwana (ZILLZELL MEDIA PRIMA, 2023)
The purpose of this study is to find out how community participation in paying the PBB within the framework of cultural values of local wisdom (Alempureng and Assitinajang in Soppeng Regency). The primary data in this study was obtained from interviews with the resource persons, namely the people of Soppeng Regency. This type of research is referred to in qualitative research carried out with an interpretive phenomenology approach. The results showed that some people in Baringeng Village, Soppeng Regency lacked obedient and honest awareness of the importance of paying the PBB. Many people do not understand the importance of paying the PBB itself and are more concerned with other needs that they think are far more important. Factors such as education, age and income turned out to be one of the deterring factors because the village was unable to provide efforts to be on time to pay the PBB.